Identificação molecular de espécies de Fusarium e genes preditivos de micotoxinas associados aos grãos de milho e trigo no centro-sul do Brasil - Silva, Cleiltan Novais da (2011)
Diseases caused by Fusarium spp. on maize (Zea mays) and wheat (Triticum aestivum) ears decrease grain yield and quality. The objectives of this research were: (i) to identify Fusarium species associated with maize grains aiming to determine their prevalence in different producing areas of Central and Southern Brazil; and (ii) to determine their pathogenicity on maize; (iii) to characterize F. graminearum complex (Fg complex) isolates from wheat collected in the State of Paraná for predictive genes for trichothecenes synthesis. For this, it was analyzed 353 isolates from maize and 135 isolates from wheat. In maize, the identification of species was based on PCR using species-specific primers or partial sequencing of the elongation factor-1alpha gene, followed by blast search at the Fusarium-ID site.The most frequent species was F. verticillioides (85.9%), followed by Fg complex (11.3%), F. equiseti (1.4%), F. subglutinans (0.84%), and F. andiyazi (0,56%). Fusarium verticillioides was the prevalente species in all regions. The Fg complex was found only in the states of Santa Catarina, Paraná, Minas Gerais, and São Paulo; F. equiseti was found in Goiás, São Paulo, and Mato Grosso; and F. subglutinans was found in Goiás and Paraná. Most of the Fg complex isolates (68.5%) were found in areas with altitudes above 600 meters. The trichothecenos genotypes found in maize were nivalenol (NIV) (87,5%) and 15-acetildeoxynivalenol (15-ADON). The 3-acetildeoxynivalenol (3-ADON) genotype was not found. On seedlings, the species F. verticillioides and F. subglutinans, and the NIV e 15-ADON genotypes of Fg complex caused necrosis on roots and reduction in growth an dry weight. In wheat, all isolates belonged to the Fg complex. The 15-ADON and NIV genotypes were found in the three wheat producing regions of Paraná State; however, the proportion NIV/15-ADON was higher in the West, Central West and North Regions than in the Southern Region. The 3-ADON genotype was not found.